Increasing Customer Loyalty Through E-Service Quality and Satisfaction: A Study on Muamalat Islamic Digital Applications - Umar, St Hafsah; T, Andi Marhuni (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
Technological advances have made it easier for various business activities, including production, marketing, sales, and transactions. Technology has given birth to terms such as E-business and E-commerce, changing the way transactions are carried out without the need for a physical presence or cash payment. Now, cashless transactions can be made quickly and efficiently through mobile devices connected to the internet. This study aims to examine the influence of E-Service Quality on Customer Loyalty with Customer Satisfaction as an Intervening Variable. Using a quantitative approach with 186 samples of M-DIN users at Bank Muamalat KCP GOWA, data analysis was carried out through descriptive statistical analysis and path analysis. The results show that E-Service Quality has a positive and significant effect on Customer Loyalty, and Customer Satisfaction can mediate this influence on MDIN users.